Especificação de uma arquitetura para migração de máquinas virtuais utilizando ontologias - Rohden, Rafael Barasuol (2015)
Cloud computing is a new area in computing, providing new perspectives in the area of interconnect technologies and raises issues in architecture, design and implementation of existing networks and data centers. Currently through technology like server virtualization, has been widely used for providing on-demand services with avoiding the spreading of servers. In this way the servers are used so that its resources be better used to ensure the availability of resources and services for users, enabling, so these users from accessing services based on your needs, regardless of where the services are hosted, or how they are delivered. This being, the main feature of cloud computing. However, some servers become eventually overloaded and others are more idle, and the way to solve this is by using the migration of virtual machines in real time, that is, perform the migration of running virtual machine along with its applications to another server by restoring the balance of the servers. This balance, called load balancing is one of the techniques used by real-time migration technology. That is, the technology of migration of virtual machines in real time has become the key to optimizing computer resources. Thus, it becomes interesting the development of solutions that enable the deployment of this technology. Through a virtualized environment where applications monitors check the load state of the servers it is possible to interact with the virtual machines performing migration to ensure the optimization and utilization of computational resources. Considering this, this work presents an architecture for migration of virtual machines, which uses ontologies for knowledge representation in a virtualization environment. For this, was developed, through the process Ontology Development 101, an ontology, Onto-LM, which represents a virtual machine virtualization environment which offers help to visualize current state of the environment. For the specified architecture in this work was delimited components and their respective information flows between a component and another. Use of ontologies as one of its components. For examples of this architecture has been developed a tool, OntoMig, in the JAVA programming language, which allows to run and manage the information acquired from monitoring of servers, the charge of the ontology and the migration of virtual machines when needed.